PENGARUH PENERAPAN QUALITY MANAGEMENT SYSTEM TERHADAP KUALITAS SUMBER DAYA MANUSIA PADA PT. CASUARINA HARNESSINDO BEKASI - Niken Widyastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
This research aim for given prove empirically effect application role of quality management system to factor or variable that influence quality human resources development. This research carry out in PT. Casuarina Harnessindo – Bekasi, with use population with amount 30 respondent with use census sample draw method: sample drawing where all population amount become sample so that amount sample within this research have amount 30 respondent. Data collection technique use documentation and questioner. Data analysis method use research instrument test use validity test and reliability test, hypothesis test consist multiple linear regression, determinan coefficient, test t analysis and F test, classic assumption test consist normality, multicolienearity, heterokesdasity and autocorrelation. Research result show that hypothesis 1 that reveal present significant effect employee role, leader role, relationship leader with employee organization aspect and environment aspect within application ISO quality Management System 9001 – 2000 toward quality of employee resources simultan proved within this research, hypothesis 2 that reveal that present significant effect employee role within application ISO quality Management System 9001 – 2000, toward quality employee resources proved within this research, hypothesis 3 that reveal that present significant effect leader role within application ISO quality Management System 9001 – 2000, toward quality employee resources proved within this research, hypothesis 4 that reveal present significant relationship leader with employee within application ISO quality Management System 9001 – 2000, toward quality employee resources proved within this research, hypothesis 5 that reveal present significant organization aspect role within application ISO quality Management System 9001–2000, toward quality employee resources not proved within this research, hypothesis 6 that reveal present significant environment aspect role within application ISO quality Management System 9001– 2000, toward quality employee resources not proved within this research.